Detection of microplastics in bottled drinking water - Noor, Farah Mohd (Universiti Sains Malaysia, 2025)
as a significant concern, particularly regarding its potential implications for product safety and consumer health. This study aimed to evaluate the leaching of MPs under different conditions, including temperature variations at room temperature (25 ± 2°C) and peak temperature (60 ± 2°C), mechanical stress at two shaking speeds (30 RPM and 60 RPM), and repeated usage of drinking bottled water. Additionally, the study characterized the morphology of the leached MPs. Results revealed that peak temperatures and increased mechanical stress significantly enhanced MPs release, with peak leaching observed at 60°C and 60 RPM. Repeated use further amplified the release, indicating that thermal and mechanical degradation play critical roles in the fragmentation of MP particles. The most commonly observed MP shapes were pellets, fibers, and filaments, with transparent MPs dominating across all tests, reflecting the material of the bottles. This study highlighted the awareness to the consumer on the critical impact of thermal, mechanical stress and repeated use of drinking bottled water through temperature test at two different temperatures (25 ± 2 and 60 ± 2°C), shaking test at 30 RPM and 60 RPM, and the reusability test, on the release of MPs from single-use bottled drinking water.